Behavior usage model to manage the best practice of e-learning - Chayanukro, Songsakda; Mahmuddin, Massudi; Husni, Husniza (2012)
This study aims to find e-Learning users’ behavior model that use data mining techniques to predict the successful learning behavior in utilizing e-Learning systems and to develop appropriate e-Learning users’ behavior models that could be used broadly in other higher institutions. Due to the lack of suitable e-Learning user’s behavior model for open source e-Learning system (Moodle) that could not be able to make a prediction for learning outcomes or performances.In this case, it is not useful enough for improving learners’ performance which may cause failure in learning.Therefore, this research is conducted upon three main phases, which are data preparation, data extraction and model verification for generating a verification pattern. This pattern could be used as a direction for creating a more appropriate e-Learning users’ behavior model.